Interaction between the nervous and skeletal systems - Xu, Jiajia; Zhang, Zhongmin; Zhao, Junjie; Meyers, Carolyn A.; Lee, Seungyong; Qin, Qizhi; James, Aaron W. (Frontiers in Cell and Developmental Biology, 2022)
The skeleton is one of the largest organ systems in the body and is richly innervated by the network of nerves. Peripheral nerves in the skeleton include sensory and sympathetic nerves. Crosstalk between bones and nerves is a hot topic of current research, yet it is not well understood. In this review, we will explore the role of nerves in bone repair and remodeling, as well as summarize the molecular mechanisms by which neurotransmitters regulate osteogenic differentiation. Furthermore, we discuss the skeleton's role as an endocrine organ that regulates the innervation and function of nerves by secreting bone-derived factors. An understanding of the interactions between nerves and bone can help to prevent and treat bone diseases caused by abnormal innervation or nerve function, develop new strategies for clinical bone regeneration, and improve patient outcomes.